2005
DOI: 10.17660/actahortic.2005.705.8
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Evolution, and Biogeography of Juglans: A Phylogenetic Perspective

Abstract: Phylogenetic analyses of extant species of Juglans (Juglandaceae) with the New and Old World distributions were performed using five cpDNA intergenic spacer (IGS) sequences (trnT-trnF, psbA-trnH, atpB-rbcL, trnV-16S rRNA, and trnS-trnfM) to elucidate the origin, diversification, historical biogeography, and evolutionary relationships within the genus. Overall, 3848 characters were sampled, yielding 105 (2.7%) variable sites, of which, 45 (1.16%) were potentially parsimony informative. In all, seventeen in-grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
13
1
1
Order By: Relevance
“…In the field, J. sigillata individuals are distinguished from J. regia by their relatively large compound leaves, rugose trunks, thick endocarp, and deeply pitted nut surfaces (Dode, 1909; Stone, 1993). Previous studies based on DNA sequence data from five chloroplast intergenic spacers demonstrated marginal differences between J. regia and J. sigillata (Aradhya et al, 2006). However, a recently published study of J. regia and J. sigillata from central and southwestern China (Wang et al, 2008), based on different microsatellite loci than those employed in this study, failed to distinguish J. regia from J. sigillata , leading Wang et al to suggest that J. regia and J. sigillata belong to the same species.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the field, J. sigillata individuals are distinguished from J. regia by their relatively large compound leaves, rugose trunks, thick endocarp, and deeply pitted nut surfaces (Dode, 1909; Stone, 1993). Previous studies based on DNA sequence data from five chloroplast intergenic spacers demonstrated marginal differences between J. regia and J. sigillata (Aradhya et al, 2006). However, a recently published study of J. regia and J. sigillata from central and southwestern China (Wang et al, 2008), based on different microsatellite loci than those employed in this study, failed to distinguish J. regia from J. sigillata , leading Wang et al to suggest that J. regia and J. sigillata belong to the same species.…”
Section: Discussionmentioning
confidence: 94%
“…Juglans regia and J. sigillata were designated as the sole members of section Juglans (section Dioscaryon Dode); the other Asian Juglans species, J. ailantifolia and J. mandshurica , are classified within section Cardiocaryon . Subsequent molecular work based on chloroplast sequence data supported the sister‐group relationship of J. regia and J. sigillata (Aradhya et al, 2006). However, Wang et al (2008), using different microsatellite markers, were unable to distinguish between the two species in southwestern China, and they concluded that these two should be considered a single species.…”
mentioning
confidence: 85%
“…Aradhya et al (2007) used ITS, RFLP, and cpDNA sequence data to suggest J. regia and J. sigillata are distinct species. J. cathayensis and J. mandshurica were combined into one species in Flora of China (English version) (Lu et al, 1999), which does not consider J. hopeinesis (Kuang and Lu, 1979; Aradhya et al, 2004, 2007) a valid taxon. In addition, some previous phylogenetic studies of Juglans omitted J. hopeiensis and J. sigillata (Fjellstrom and Parfitt, 1995; Stanford et al, 2000; Aradhya et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…J. regia and J. sigillata are readily distinguishable from each other based on nut morphology, that J. sigillata has seal‐like depressions on the surface of the nuts, whereas J. regia has a wrinkled nut surface. However, at the species level, these two Juglans exhibit a closest relationship, they have similar morphologic and chloroplast sequences, and even indistinguishable microsatellite markers . Because of the shell of iron walnut hard to be separated, it is not suitable as a dietary nut.…”
Section: Introductionmentioning
confidence: 99%